A multifunctional nanoplatform for cancer chemo-photothermal synergistic therapy and overcoming multidrug resistance. (7th March 2018) - Peng, Yunmei; Nie, Junpeng; Cheng, Wei; Liu, Gan; Zhu, Dunwan; Zhang, Linhua; Liang, Chaoyu; Mei, Lin; Huang, Laiqiang; Zeng, Xiaowei
Abstract : A multifunctional nanoplatform could overcome multidrug resistance and showed cancer chemo-photothermal synergistic therapy with the near-infrared irradiation. Abstract : The integration of various therapy strategies into a single nanoplatform for synergistic cancer treatment has presented a great prospect. Herein, docetaxel (DTX)-loaded poly lactic- co -glycolic acid (PLGA)-coated polydopamine modified withd -α-tocopherol polyethylene glycol 1000 succinate (TPGS) was synthesized for chemo-photothermal synergistic therapy against cancer. Firstly, the DTX-loaded PLGA NPs were prepared by a facile and robust nanoprecipitation method. Then, they were coated with dopamine to achieve the photothermal effects and to be further modified with TPGS, which can inhibit the P -glycoprotein-mediated multidrug resistance (MDR). The near-infrared (NIR) laser irradiation triggered DTX release from DTX-loaded PLGA NPs@PDA-TPGS, and then the chemo-photothermal therapy effect could be enhanced. The in vitro experimental results illustrated that DTX-loaded PLGA NPs@PDA-TPGS exhibits excellent photothermal conservation properties and remarkable cell-killing efficiency. In vivo antitumor studies further confirmed that DTX-loaded PLGA NPs@PDA-TPGS could present an outstanding synergistic antitumor efficacy compared with any monotherapy. This work exhibits a novel nanoplatform, which could not only load chemotherapy drugs efficiently, but could also improve the therapeutic effect of chemotherapy drugs by overcoming MDR and light-mediated photothermal cancer therapy.